Formation of DNA adducts in skin, lung and lymphocytes after skin painting of rats with undiluted bitumen or coal-tar fume condensates - Genevois, Cyril; Brandt, H. C. A.; Bartsch, Helmut; Obrecht-Pflumio, S.; Wild, C. P.; Castegnaro, M. (Polycyclic aromatic compounds, 1996)
During the hot application of bitumen-containing materials, e.g. in road paving or roofing, fumes are emitted that contain traces of polycyclic compounds. Although worker exposures to these fumes are low, they might lead to health problems. Bitumens have been classified by IARC in group 3 (compounds not classifiable as to their carcinogenicity to humans) and extracts of steam-refined and air-refined bitumens in group 2B (possible human carcinogens). Carcinogenicity and genotoxicity experiments by skin painting have to date always involved dilution of bitumens or their fume condensates in solvents. In order to determine whether undiluted bitumen fume condensates (BFCs) are potentially genotoxic to humans, these were produced by trapping the particulates on a glass fibre filter and the semi-volatiles (vapours) on XAD-2 resin. the benzene soluble matter (BSM) from the particulates phase was combined with the diethyl ether extract of the XAD resin that contained the semi-volatiles. the ether was evaporated, the resulting BFC was analysed for its PAH content and applied twice two days apart to the skin of BD4 rats. During the experiment the animals were housed individually in metabolic cages and the urines were collected and analysed for 1-hydroxypyrene. Twenty-four hours after the lastt treatment, the animals were sacrificed and the skin, lung and lymphocytes were collected. DNA was extracted and DNA adducts were analysed by 32P-postlabelling with the objective of determining whether lymphocytes can be used as biomarkers of skin exposure to BFCs. As a reference material, fume condensates from coal tar (IARC, classification group 1, human carcinogens) were subjected to the same tests. Skin penetration of the fume condensates was rapid, possibly due to a lowering of the viscosity by the mixing of the semi-volatiles and the particulates. All fume condensates displayed genotoxicity under the conditions of preparation described above. A linear relation exists between 1-hydroxypyrene excretion and the pyrene content of the fumes, but no relation between these parameters and adduct formation was found. Qualitatively, the adduct patterns from the BFCs are very different from those of the coal tar fume condensates. Some of the adducts found in the lymphocytes may be used as a marker of exposure to bitumen fumes. the unsubstituted PAH from the EPA list are not the sole genotoxic compounds in BFC responsible for adduct formation; the relative contribution of each class of heterocyclic PAC should be further investigated.
Elektronische Reproduktion der Druck-Ausgabe 5. Oktober 2006
Gesehen am 10.01.2024